The Factors Influence Customer Purchase Intention on Cause-Related Marketing in Sadari Sedari - Rusdiansyah, Fadel Rasyid; Chaldun, Evy Rachmawati (Journal of Business and Management, 2021)
Sadari Sedari is A nonprofit organization that comes with the aim to strive for education and environmental sustainability through selling secondhand clothes collected from society. Their revenue is a fundamental thing towards their donation amount. Behind the selling activity, the heaps of used-clothes piled up in their storage because of the items that are not sold is become their concern. This study aims to discover the factors that influence customer purchase intention on cause-related marketing in Sadari Sedari and trace the linkage between them. The Theory of Planned Behavior (TPB) is used with additional variables of cause involvement and brand-cause fit. The survey collected 205 respondents within the age dominated of 18-23, domiciled in Jabodetabek and Bandung. The data processed with the PLS-SEM method. The research found the most significant influence to purchase intention is on attitude that affected by brand-cause fit. The research designed with the case study of Sadari Sedari and could be a reference for nonprofit organizations, or businesses to develop a cause-related marketing initiatives. Moreover, these findings could be a reference for researchers to use TPB to evaluate customer purchase intention in cause-related marketing activity.Keywords: Cause-Related Marketing, Consumer Behavior, Non-Profit Organization, Purchase Intention, Sadari Sedari, Theory of Planned Behavior (TPB)